Regional Sustainable Tourism for Developing the Ecotourism - Fafurida, (International Journal of Psychosocial Rehabilitation, 2020)
Abundant and beautiful natural wealth in Central Java Province, Indonesia is a natural asset for tourism sector. The problem raised is the tradeoff between the increase in income from the tourism sector and the risk of damage to nature, due to the increased efficiency of the tourism. This study aims at: 1) Analyzing the potential of nature-based tourism in the province of Central Java; (2) Analyzing sustainable tourism development strategies. These objectives were carried out using descriptive analysis, and IFAS (Internal Factor Analysis Strategy) and EFAS (External Factor Analysis Strategy) methods to analyze strategies. The results of the study show a map of nature-based tourism potential in Central Java based on the district and its characteristics analysis. Strategies based on internal factors (IFAS) and external factor analysis strategies (EFAS) include: Development of tourism in Central Java requires an aggressive strategy by fostering ecological enthusiasm and conservation of nature from the beginning at every level of education. Improving the quality of human resources in the tourism sector. Massive education is needed about the need for ecosystem preservation for domestic and foreign tourists. Support from stakeholders at the central and regional levels has an important role. Development of education that accommodates nature conservation curriculum material and the concept of ecotourism. Technology development to provide tourism information, especially for people who currently have a lifestyle back to nature.